Apriori Algorithm Based Component Classifications and Adaptation for Software Reuses - Korra, Sampath (Indian Journal of Computer Science, 2022)
With the growth in software development, the software user expects high-quality software services with lesser time complexity. Therefore, the demand for software component based development is also increasing. In the recent past, a good number of research attempts have tried to build an automated framework for generating the recommendations for component equivalence. In software engineering and program building, reusability is the utilization of existing resources in some structure inside the product items. Adaptive software reuse products improve the life cycle of software and enhance the planning, coding, and documentation in different approaches of reusability. On the other hand, reusability can be used to meet with new software demands. Thus, the proposed novel approach to Apriori based component classifications and adaptation is used to software component reusability based on the recommendation of rule-based analysis.